From administrative hospital management to performancebased management: Paradigm shift at the Yaoundé Gynaeco-Obstetric and Pediatric Hospital, Cameroon - Fru Angwafo III; Andreas Chiabi; Assumpta Bella; Evelyn M. Mah; Julius S. Dohbit; Willy Tafen; Immaculate Bih Geh; Samuel Lele; Charles N. Mba; François-Xavier (AOSIS, 2020)
The Yaoundé Gynaeco-Obstetric and Pediatric Hospital (YGOPH) faced challenges of high debts and sub-optimal care delivery. Performance-Based-Management (PBM) provides an environment of checks and balances, increased transparency, competition and autonomy, thereby improving clinical as well as financial indicators. We describe the transition from resource-based to PBM at the YGOPH over a seven-year period. There was an increase of 4.5% in OB/GYN and 8.1% in prenatal consultations, 8.4% in C-sections, 6.1% of children vaccinated, and 30.5% of women seen for family planning, 51.1% of people living with the Human Immunodeficiency Virus on treatment and 29.4% of indigent patients. These results occurred in spite of a 14% reduction in staff. Annual revenue increased by 5.75%. The share of hospital income from care on overall hospital revenue increased from 55.11% to 60.00%. With this self-financing PBM model, the hospital remains a social, humane and financially viable structure delivering improved quality care.